24-hour Ambulatory Blood Pressure is Linked to Chromosome 18q21-22 and Genetic Variation of NEDD4L Associates with Cross-Sectional and Longitudinal Blood Pressure in Swedes. - Fava, Cristiano; Wowern, Fredrik; Berglund, Göran; Carlson, Jonas ; 0000-0002-9135-9814; Hedblad, Bo; Nilsson, Lena; Burri, Philippe; Almgren, Peter; Melander, Olle ; 0000-0002-2581-484X (Kidney International, 2006)
Numerous linkage studies have indicated chromosome 18q21–22 as a locus of importance for blood pressure regulation. This locus harbors the neural precursor cell expressed developmentally downregulated 4-like (NEDD4L) gene, which is instrumental for the regulation of the amiloride-sensitive epithelial sodium channel (ENaC). In a linkage study of 16 markers (including two single nucleotide polymorphism markers located within the NEDD4L gene) on chromosome 18 between 70–104 cM and ambulatory blood pressure (ABP), in 118 families, the strongest evidence of linkage was found for 24 h and day-time systolic ABP at the NEDD4L locus (82.25 cM) (P=0.0014). In a large population sample (n=4001), we subsequently showed that a NEDD4L gene variant (rs4149601), which by alternative splicing leads to varying expression of a functionally crucial C2 domain, was associated with diastolic blood pressure (DBP) (P=0.03) and DBP progression over time (P=0.04). A genotype combination of the rs4149601 and an intronic NEDD4L marker (rs2288774) was associated with systolic blood pressure (SBP) (P=0.01), DBP (P=0.04), and progression of both SBP (P=0.03) and DBP (P=0.05) over time. A quantitative transmission disequilibrium test in the family material of the rs4149601 supported this NEDD4L variant as being at least partially causative of the linkage result. In conclusion, our findings suggest that the chromosome 18 linkage peak at 82.25 cM is explained by genetic NEDD4L variation affecting cross-sectional and longitudinal blood pressure, possibly as a consequence of altered NEDD4L interaction with ENaC.
Keywords: blood pressure; linkage; NEDD4L; genetics